THE RELATIONSHIP BETWEEN RENEWABLE ENERGY CONSUMPTION AND HUMAN DEVELOPMENT - Aliona Balan (Economy and Sociology)
This article examines the relationship between renewable energy consumption and human development indicators in Moldova. The analysis, spanning from 1995 to 2021, employs econometric techniques, including Ordinary Least Squares (OLS) and Two-Stage Least Squares (2SLS) regression, to investigate the impact of renewable energy on the Human Development Index (HDI). The findings reveal a positive correlation between renewable energy consumption and HDI, indicating that increased adoption of renewable energy is associated with improvements in human development. Specifically, the study finds that a one-percentage-point increase in renewable energy consumption leads to approximately a 1.6% increase in HDI. Moreover, the article discusses Moldova's energy policy landscape, highlighting initiatives and policies aimed at promoting renewable energy development and achieving sustainability goals. The conclusions drawn from this study emphasize the critical importance of prioritizing renewable energy solutions. Such prioritization is deemed essential for driving sustainable development, fostering economic growth, bolstering energy security, and mitigating the adverse impacts of climate change. The study underscores that Moldova's experience and policy initiatives could serve as a valuable model for other nations aiming to enhance their human development through sustainable energy practices. This research argues for a continued and intensified focus on the integration of renewable energy, highlighting its fundamental importance within national and international strategies aimed at achieving ambitious human development and sustainability goals. This involves a reassessment and expansion of current commitments, considering not only the ecological benefits, but also the long-term economic and social impact, thereby strengthening a sustainable future for future generations.